Scooby-Doo! World of Mystery 26 Chile - Easter Island - Craft Plus Publishing Ltd (De Agostini Uk Ltd, 2005)
Two arguing professors,some huge stone heads and a scary birdman all add up to a big mystery for the gang.
Keywords: Juvenile literature-Fiction